2021
DOI: 10.1177/0020720920988493
|View full text |Cite
|
Sign up to set email alerts
|

Distance learning in engineering education: Challenges and opportunities during COVID-19 pandemic crisis in Pakistan

Abstract: This paper analyzes the impact of remote classrooms and labs as an outcome of “social distancing” during COVID-19 outbreak. It is important to analyze the emergence of web technologies and tools available for online learning and its impact on engineering education. The intended focus is to find a way out to address the issues regarding continued teaching and learning during long academic breaks due to this unpredicted pandemic. Some challenges in developing economies include the unavailability of internet serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 31 publications
2
41
0
3
Order By: Relevance
“…Considering the importance of teachers’ self-efficacy in an effective ICT integration, several studies have suggested developing their pedagogical and technological skills by establishing training programs. The study by Khan and Abid (2021) revealed that the paradigm shift from face-to-face to online teaching-learning during the COVID-19 phase gave an advantage for teachers and students to acquire technological skills by using different digital tools and platforms. They also advocated employing an online certification decision matrix (OCDM) to assure online teaching effectiveness and readiness of teachers.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the importance of teachers’ self-efficacy in an effective ICT integration, several studies have suggested developing their pedagogical and technological skills by establishing training programs. The study by Khan and Abid (2021) revealed that the paradigm shift from face-to-face to online teaching-learning during the COVID-19 phase gave an advantage for teachers and students to acquire technological skills by using different digital tools and platforms. They also advocated employing an online certification decision matrix (OCDM) to assure online teaching effectiveness and readiness of teachers.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the relatively high satisfaction rate among medical students toward virtual public health field visits in this study, medical training needs face-to-face experiences and student-tutor interactions, which will still be limited in virtual learning. It is worthwhile to note that many tertiary education programs, particularly in engineering, have already accepted the new norm in learning as a mixture of hybrid and virtual learning ( 25 , 26 ). However, within the context of learning public health concepts, we believe that hands-on training along with virtual learning would be more suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Authors in [10] analysed the benefits and proposed the use of augmented reality (AR) in online delivery of power engineering education during pandemic. However, authors in [25] highlighted some key challenges such as the unavailability of internet service, and limited resources accessibility during the COVID-19 outbreak, which is also experienced by many students in Brazil [26]. Authors highlighted that there is a lack of policy guidelines for online delivery of engineering courses and assessment techniques for quality teaching.…”
Section: Globally Observed Covid-19 Challenges On Educationmentioning
confidence: 99%